Analisis Faktor Yang Berkaitan Dengan Kinerja Kader Posyandu: Studi Pada Kelompok Kader Posyandu di Wilayah Puskesmas Pamotan Kabupaten Rembang - Yuwanita Nurhayati; Mamik Indrayani; Mochamad Edris (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to analyze the factors that influence the performance of Pamotan Health Center Posyandu Cadres. This research uses a qualitative research approach. This qualitative research uses natural settings to interpret phenomena that occur and is carried out using existing methods. The qualitative approach in this research describes intensively, the researcher participated for a long time in the field, carefully recorded what happened, carried out reflective analysis of various documents found in the field. Data collection techniques through observation, interviews and documentation directly by researchers, as well as data analysis techniques using the Miles & Huberman model explain that activities in qualitative data analysis use 3 types of activity steps which are carried out continuously until complete with the steps, namely data reduction (data reduction), data presentation (data display), and conclusion/verification. The research findings show that there is a significant relationship between the level of knowledge, motivation, infrastructure and training with cadre performance in implementing posyandu activities and infrastructure is the factor most related to cadre performance in implementing posyandu activities.